Anthropogenic Atmospheric Air and Children’s Health (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Anthropogenic environmental pollution has a pronounced effect on the formation of population health, especially in connection with changes in socio-economic conditions. Recent studies suggest that the polluted environment is one of the important factors determining the changes in the health status of the urban population.